Evaluation of Phase Feeding and Complete Diet Blending on Growing-Finishing Pigs’ Growth Performance and Diet Economics - Ron Aldwin S. Navales; Mike D. Tokach; Mike E. Reard; Alan J. Warner; Chad Hastad; Joel M. DeRouchey; Katelyn N. Gaffield; Jordan T. Gebhardt; Robert D. Goodband; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 962 pigs [Fast LW × PIC L02 × PIC 800; initially 58.4 ± 0.81 lb] were used in a 116-d study to compare feeding strategies (phase feeding vs. diet blending) on growing-finishing pig growth performance and diet economics. Pens of pigs were randomly assigned to one of two treatments following a randomized complete block design with barn and initial BW as blocking factors. The treatments included two feeding programs, a phase feeding strategy or complete diet blending with pre-defined mixing proportions of two diets to meet 100% of the SID Lys curve requirement estimates for 50- to 250-lb pigs. The experimental period spanned from 50 to 250 lb BW, and a common feeding period from 250 to 300 lb BW. Diets in phase feeding strategies were provided from 50 to 100, 100 to 175, and 175 to 250 lb. Pigs were fed on a feed budget set at 97, 181, and 230 lb of feed per pig for phases 1 to 3, respectively. During the common period, all pigs received the same DDGS-free diet. Feeding strategy did not influence BW or ADG at any time during the study, except for BW at d 56 and ADG on d 28 to 56, where pigs in the phase feeding group had greater (P ≤ 0.013) BW and ADG compared to the diet blending group. For ADFI, pigs fed the diet blending strategy had lower (P ≤ 0.017) ADFI than those fed by phase feeding both during experimental and overall periods, but not during the common period. Pigs fed by diet blending had improved (P = 0.012) feed efficiency compared to pigs fed the phase-feeding strategy during the experimental period but not overall. During the common feeding period (d 84 to 102), F/G of pigs previously phase fed was improved (P = 0.029) compared to pigs previously fed the diet-blending strategy. Consistently, caloric efficiency was improved (P = 0.007) with the diet-blending strategy compared to the phase-feeding strategy during the experimental period. For diet economics, pigs fed the diet-blending strategy tended to have lower feed cost per pig and per lb of gain (P = 0.078 and 0.083, respectively) than those fed the phase-feeding strategy during the experimental period, but not during the overall period. Feeding strategy had no effect on total revenue or IOFC in either period. In conclusion, diet blending improved F/G by reducing ADFI without affecting ADG during the blending strategy feeding period. However, the inclusion of a common diet diminished the F/G advantage, resulting in similar overall IOFC between the two feeding strategies.
Keywords: Diet blending; growing-finishing pigs; phase feeding